Griefing emotions on Facebook wall: a visual multimodal dialogue from a semiotic technology perspective - Nasrullah, Rulli; Kontu, Study Rizal L.; Murodi; Jumroni; Musyarrofah, Umi; Adi, Wasono (Fakultas Dakwah UIN Saizu Purwokerto, 2025)
The expression of grief has shifted from traditional face-to-face rituals to digital spaces. Social media provides features such as emojis, stickers, and GIFs, enabling users to express mourning visually and symbolically. This phenomenon illustrates how cultural and religious practices are transformed through technological mediation. The study aims to analyze how multimodal dialogue represents grief on Facebook and how meaning is constructed in digital mourning practices. The research applies a social semiotic approach with a semiotic technology method. Data were collected from grief-related posts and comments on the Facebook account @endah.sucipto. The analysis focused on two models of interaction: system–user and user–user. Each textual and visual element was examined through multimodal content analysis and interpreted using semiotic theory. The findings show that expressions of grief appear in three dominant forms: condolences, Qur’anic verses, and prayers for the deceased. Users also rely on emojis, reaction icons, stickers, and images to strengthen emotional expression. These multimodal practices integrate religious traditions and digital symbols, creating hybrid forms of mourning in online communities. Visual features such as GIFs and stickers are substitutes for nonverbal cues and add affective value to brief textual comments. This study contributes to communication and cultural studies by showing how social media functions as both a technological medium and a cultural arena. The results highlight the role of digital semiotics in rearticulating cultural symbols of grief. Future research may expand this inquiry by comparing digital mourning practices across platforms and cultural contexts.